2021
DOI: 10.1128/spectrum.00695-21
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Bacterial Pneumonia in Critically Ill Patients with COVID-19 Using a Multiplex PCR Assay: A Large Italian Hospital’s Five-Month Experience

Abstract: Since bacterial pneumonia is relatively frequent, suspicion of it in COVID-19 patients may prompt ICU clinicians to overuse (broad-spectrum) antibiotics, particularly when empirical antibiotics do not cover the suspected pathogen. We showed that a PCR-based, culture-independent laboratory assay allows not only accurate diagnosis but also streamlining of antimicrobial therapy for bacterial pneumonia episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
4
17
0
1
Order By: Relevance
“…This figure varies widely across the aforementioned studies, likely reflecting differences in bacterial targets present in the specimens and EAT usage at time of testing [16] . Similarly, in line with previously published data [ 8 , 13 , [15] , [16] , [17] , 21 ], use of FA-PP increased the detection of antimicrobial-resistant bacteria.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This figure varies widely across the aforementioned studies, likely reflecting differences in bacterial targets present in the specimens and EAT usage at time of testing [16] . Similarly, in line with previously published data [ 8 , 13 , [15] , [16] , [17] , 21 ], use of FA-PP increased the detection of antimicrobial-resistant bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…This provides further proof that FA-PP increases the bacterial detection yield compared with standard culture. These figures were higher than those previously published by Buchan et al ., (94.8% and 63.3%) [16] , and Lee et al ., (a 70.3% increase in total bacterial targets detected by the PN panel) [21] , probably due to the extensive use of EAT among patients in the current study. In our experience, the PPA between qualitative results returned by FA-PP and standard culture was 44% overall, and higher for Enterobacterales compared with NF-GNB, other GNB and GPC.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…During the COVID-19 pandemic, Maataaoui et al revealed in a prospective cohort of 112 episodes (104 HAP-VAP) an early empirical therapeutic change in 34% of HAP-VAP episodes (of which 46.3% were withdrawn) when this panel was performed [106]. Another recent prospective study showed among COVID-19 ICU patients that antibiotics were initiated in 87 (72.5%) of 120 pneumonia episodes and were not administered in 80 (87.0%) of 92 non-pneumonia episodes based on FA results [107].…”
Section: Moving From An Empirical To Oriented Antimicrobial Choicesmentioning
confidence: 99%